Martian aeolian activity at the Bagnold Dunes, Gale Crater: The view from the surface and orbit. Issue 10 (21st October 2017) - Bridges, N. T.; Sullivan, R.; Newman, C. E.; Navarro, S.; van Beek, J.; Ewing, R. C.; Ayoub, F.; Silvestro, S.; Gasnault, O.; Le Mouélic, S.; Lapotre, M. G. A.; Rapin, W.
Abstract: The first in situ investigation of an active dune field on another planetary surface occurred in 2015–2016 when the Mars Science Laboratory Curiosity rover investigated the Bagnold Dunes on Mars. High Resolution Imaging Science Experiment images show clear seasonal variations that are in good agreement with atmospheric model predictions of intra‐annual sand flux and migration directions that together indicate that the campaign occurred during a period of low wind activity. Curiosity surface images show that limited changes nevertheless occurred, with movement of large grains, particularly on freshly exposed surfaces, two occurrences of secondary grain flow on the slip face of Namib Dune, and a slump on a freshly exposed surface of a large ripple. These changes are seen at Martian solar day (sol)‐to‐sol time scales. Grains on a rippled sand deposit and unconsolidated dump piles show limited movement of large grains over a few hours during which mean friction speeds are estimated at 0.3–0.4 m s −1 . Overall, the correlation between changes and peak Rover Environmental Monitoring Station (REMS) winds is moderate, with high wind events associated with changes in some cases, but not in others, suggesting that other factors are also at work. The distribution of REMS 1 Hz wind speeds shows a significant tail up to the current 20 m s −1 calibration limit, indicating that even higher speed winds occur. Nonaeolian triggering mechanisms are also possible. The low activity period at the dunes documented by Curiosity provides clues to processes that dominated in the Martian past under conditions of lower obliquity. Plain Language Summary: The modification of Martian sand dunes and nearby areas by the wind is monitored from the surface by the Curiosity rover and from orbit by the High Resolution Imaging Science Experiment camera. When the rover was at the dunes, changes were small but still showed moving grains and slumps. The results indicate that surface changes occur even in low activity periods, providing insight into past Martian climates. Key Points: Dune activity observed on the surface of Mars Changes seen from Mars orbit and surface First estimate of wind threshold speeds on Mars in situ